Analisis Pengaruh Upah Minimum Regional (UMR) dan Indeks Pembangunan Manusia (IPM) terhadap Tingkat Pengangguran Terbuka (TPT) di Provinsi Banten dalam Perspektif Ekonomi Islam Tahun 2015-2024 - Kusuma, Rhima; Putri, Rosydalina; Hasimi, Diah Mukminatul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study analyses the effect of the Regional Minimum Wage (UMR) and Human Development Index (HDI) on the Open Unemployment Rate (TPT) from an Islamic economic perspective from 2015 to 2024 using cross-sectional data covering eight districts in Banten Province sourced from the Central Statistics Agency (BPS). This quantitative study employs the Common Effect Model. This model is deemed appropriate after passing the Chow and Hausman tests, enabling classical assumption tests, partial tests, and simultaneous tests to be conducted. The findings indicate that, partially, the UMR does not have a significant effect on the TPT. Conversely, the IPM has a significant partial effect on the TPT. Simultaneously, the UMR and IPM have a positive and significant effect on the TPT. From an Islamic economic perspective, unemployment is a social and moral issue, with an emphasis on social justice and wealth distribution. Wages are the right of workers, and improving human resource quality through the HDI is important for reducing unemployment. These results are expected to provide deeper insights into the variables studied and valuable input for formulating national economic policies aimed at reducing open unemployment in Banten Province.